Can we still afford human rights? critical reflections on universality, proliferation and costs - Bourguignon, Marie-Amélie; Lemmens, Koen; Van Poecke, Thomas; Wouters, Jan 1964- (Leuven global governance series, 2020)
This insightful book offers a critical reflection on the sustainability and effectiveness of the Universal Declaration of Human Rights (UDHR) and its legacy over the last 70 years. Exploring the problems surrounding universality, proliferation and cost, it asks the provocative question, can we still afford human rights? Expert contributors illustrate the interdependence between these three key issues in an unprecedented way, addressing many of the contemporary criticisms voiced against the human rights system and the reasons for popular skepticism about human rights. In order to interrogate the deficiencies of the UDHR, chapters analyze the following questions: Can and should we keep claiming that human rights are universal? Is their proliferation rendering human rights meaningless? And have human rights become too costly? The book concludes that there is a pressing need for a renewed and lasting commitment to human rights; we cannot afford not to afford human rights. This book will be a valuable resource for academics and students of international relations, the political sciences and comparative legal studies. Covering policy and advocacy issues as well as the evolution of case law regarding particular human rights, it will also be beneficial for policy-makers and human rights practitioners"--